Evaluation of Cryptosporidium parvum oocyst inactivation following exposure to ultraviolet light-emitting diodes by in vitro excystation and dye staining assays. (June 2022) - Matsubayashi, Makoto; Teramoto, Isao; Urakami, Itsuo; Naohara, Jun; Sasai, Kazumi; Kido, Yasutoshi; Kaneko, Akira
Abstract: Cryptosporidium spp. are protozoan parasites that are transmitted via fecal-oral routes and can exhibit chemical resistance. Chlorine resistance makes it very difficult to eliminate parasites present in contaminated drinking water. While the efficacy of ultraviolet light-emitting diodes (UV-LEDs) against microorganisms has been reported, the efficacy of UV-LEDs against Cryptosporidium spp. has not been fully evaluated. Here, we assessed the efficacy of UV-LEDs with peak wavelengths of 268, 275, 284, and 289 nm against Cryptosporidium parvum at various exposure times, with a fixed exposure distance, using two in vitro methods. Consequently, the time required for 2 log10 inactivation through the excystation method by UV-LEDs of 268, 275, 284, and 289 nm was estimated as 115.5, 104.1, 37.4, and 30.7 min, respectively. The propidium iodide (PI) and 4′, 6-diamidino-2-phenylindole (DAPI) staining assays estimated the inactivation time as 311.3, 275.2, 60.6, and 39.1 min, respectively. Our results showed that UV-LED irradiation at longer wavelengths produced higher inactivation activity against C. parvum, which corroborates our previously reported in vivo assay results, although further study is needed to clarify the mechanism. Graphical abstract: Unlabelled Image Highlights: Efficacy of UV-LED inactivation against Cryptosporidium parasites was demonstrated. Correspondence between the present in vitro assay data and previous in vivo evaluations was clarified. Irradiation by UV-LEDs at longer wavelengths showed higher inactivation activity against C. parvum .